(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Globalization and technological advancement has brought the people of the world closer together than ever before. Now, a day’s organizations are having diverse group of employees in terms of gender, ethnicity, and education background. Managing work force diversity is becoming one of the most important strategic issues for the multinational companies throughout the world. Diversity Management is a process to maintain a positive work environment where the similarities and differences of individuals are valued. The present study identifies to investigate the effect of workforce diversity on employee performance. The data were collected with the help of a questionnaire from 50 respondents working in MNCs in Faridabad city. Hypotheses and conceptual structure have been built depending on the previous studies and the results of the present study that there is statistically significant effect of the workforce diversity toward employee performance.